2014
DOI: 10.1292/jvms.13-0314
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Distributions and Changes of Angiotensin-Converting Enzyme and Angiotensin-Converting Enzyme 2 in Feline and Canine Chronic Kidney Disease

Abstract: Angiotensin-converting enzyme (ACE) is a key enzyme in the renin-angiotensin system (RAS). ACE2 is a newly identified member of the RAS. The present immunohistochemical study focused on changes in intrarenal ACE and ACE2 immunoreactivity in feline and canine chronic kidney disease (CKD). ACE immunoreactivity was predominantly observed in the brush border of the proximal tubules in dogs and cats. ACE immunoreactivity was lower in CKD kidneys than in normal kidneys, and quantitative analysis demonstrated negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…In dogs, Mitani et al [24] found that chronic kidney disease (CKD) kidneys exhibited weaker ACE immunoreactivity than normal kidneys and detected a negative association between ACE expression and renal tissue damage. However, both upregulated and downregulated ACE2 expression were detected in dogs with CKD, and ACE/ ACE2 immunoreactivity did not exhibit a close relationship with renal tissue damage [24] .…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In dogs, Mitani et al [24] found that chronic kidney disease (CKD) kidneys exhibited weaker ACE immunoreactivity than normal kidneys and detected a negative association between ACE expression and renal tissue damage. However, both upregulated and downregulated ACE2 expression were detected in dogs with CKD, and ACE/ ACE2 immunoreactivity did not exhibit a close relationship with renal tissue damage [24] .…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…In dogs, Mitani et al [24] found that chronic kidney disease (CKD) kidneys exhibited weaker ACE immunoreactivity than normal kidneys and detected a negative association between ACE expression and renal tissue damage. However, both upregulated and downregulated ACE2 expression were detected in dogs with CKD, and ACE/ ACE2 immunoreactivity did not exhibit a close relationship with renal tissue damage [24] . Burrell et al [25] suggested 76 February 6, 2015|Volume 4|Issue 1| WJN|www.wjgnet.com [30] 2003 Type 2 DM Mice ND ↓ ND ↑ 1 Ye et al [9] 2004 [14] 2006 [31] 2008 [32] 2013 Type 2 DN Humans ND ND ↑ ↑ Lely et al [34] 2004 Type 2 DN Humans ↑ ↑ ↓ ↓ Mizuiri et al [15] 2007 Type 2 DN Humans ↑ ↑ ↓ ↓ Reich et al [16] 2007 Primary glomerulopathy Humans ND ND ↑ -Lely et al [34] 2004 IgA nephropathy Humans ↑ ↑ ↓ ↓ Mizuiri et al [36] 2011 Hypertension Rats ND ND ↓ 1 Prieto et al [41] 2011 Hypertension…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…[146][147][148] The first study by 147 The second study by Mitani and colleagues evaluated ACE and ACE2 (mediates production of Ang1-7/Mas pathway) expression. ACE was identified predominantly in the proximal tubules whilst ACE2 was identified in proximal tubules and weaker staining in the distal nephron.…”
Section: Activation Of the Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…Unlike in dogs, there was no association between immunostaining of ACE or ACE2 with histopathology scores although sample numbers were small. 148 Further work and larger studies are required to confirm the association between altered expression of these components of RAAS with severity and progression of CKD.…”
Section: Activation Of the Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…High levels of ACE2 protein expression have been detected in mammalian, including human, kidney (Gembardt et al, 2005;Koka et al, 2008;Reich et al, 2008;Giani et al, 2012;Mitani et al, 2014;Grobe et al, 2015;Shi et al, 2015;Larouche-Lebel et al, 2019;Alawi et al, 2020). Strong signals were reported in the brush border of the proximal tubular cells, whereas weak to moderate signals could be found in the glomeruli, Henle's loop, distal tubules, and collecting duct (Hamming et al, 2004;Lely et al, 2004;Kamilic et al, 2010;Giani et al, 2012;Bae et al, 2015;Cao et al, 2017;Errarte et al, 2017).…”
Section: Tissue Distribution Of Ace2mentioning
confidence: 99%